Interactants and activities on Facebook, Instagram, and Twitter: Associations between social media use and social adjustment to college. Issue 1 (2nd January 2020) - Yang, Chia-chen; Lee, Yen
ABSTRACT: Research shows use of social media (SM) has important implications for college adjustment. However, most studies only focused on Facebook and did not attend to specific use patterns. Drawing on the activity-audience framework of social media use and literature of college adjustment, we examined the associations between use of Facebook, Instagram, and Twitter and college social adjustment. Regression and cluster analyses of survey data from 257 undergraduates ( M age  = 19.48) showed that SM interactants had stronger and more consistent associations with social adjustment than did activities. Using Facebook and Instagram with on-campus friends and family were related to better social adjustment; using Instagram with strangers was related to poorer adjustment. Students who frequently used all three SM to interact with off-campus friends were less adjusted than those who rarely used the platforms to interact with strangers. Some associations were moderated by SM activities. Implications of college students' development in the digital age are discussed.